2017
DOI: 10.3390/genes8060151
|View full text |Cite
|
Sign up to set email alerts
|

MYC Deregulation in Primary Human Cancers

Abstract: MYC regulates a complex biological program by transcriptionally activating and repressing its numerous target genes. As such, MYC is a master regulator of many processes, including cell cycle entry, ribosome biogenesis, and metabolism. In cancer, the activity of the MYC transcriptional network is frequently deregulated, contributing to the initiation and maintenance of disease. Deregulation often leads to constitutive overexpression of MYC, which can be achieved through gross genetic abnormalities, including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
299
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(306 citation statements)
references
References 241 publications
(342 reference statements)
4
299
0
3
Order By: Relevance
“…More interestingly, two of the regions ( 7q21.12 and 8q24.22 ) were significantly amplified in malignant samples, which lead us to discover the association of MYC , a known marker of malignancy, with the development of IPMN. The amplification and deregulation of MYC have been reported in numerous cancer studies, and its key role in metabolism, cell cycle, the biogenesis of ribosomes, and consequently, in cell growth and proliferation makes it the perfect target and marker for malignancy in IPMN detection by PJD . This finding, combined with the correlation of mutation burden with grade, has strong potential to predict the progression of IPMNs to malignancy, and exome sequencing or whole genome sequencing analysis of PJD is useful to assess the malignant risk of IPMNs.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, two of the regions ( 7q21.12 and 8q24.22 ) were significantly amplified in malignant samples, which lead us to discover the association of MYC , a known marker of malignancy, with the development of IPMN. The amplification and deregulation of MYC have been reported in numerous cancer studies, and its key role in metabolism, cell cycle, the biogenesis of ribosomes, and consequently, in cell growth and proliferation makes it the perfect target and marker for malignancy in IPMN detection by PJD . This finding, combined with the correlation of mutation burden with grade, has strong potential to predict the progression of IPMNs to malignancy, and exome sequencing or whole genome sequencing analysis of PJD is useful to assess the malignant risk of IPMNs.…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc is one of the best-studied oncogenes promoting tumorigenesis in many tissues (Kress et al, 2015;Dejure & Eilers, 2017;Kalkat et al, 2017). It is frequently over expressed in cancer, correlates with tumor aggressiveness and poor clinical outcome (Nesbit et al, 1999;Beroukhim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that induction of the c‐Myc oncogene in a nontransformed epithelial cell line induces a profound change in the pool of secreted proteins, with IGFBP‐6 and IGFBP‐7 being markedly down‐regulated . Here we extended this observation to a cellular model for breast tumorigenesis, a cancer where c‐Myc is found frequently overexpressed and is associated with poor prognosis . We show that the human nontransformed mammary epithelial cell line (MCF10A) expressing the estrogen‐inducible c‐MycER chimera (MCF10A‐MycER) undergoes a concomitant induction of IGF‐I/IGF‐II and reduction of IGFBP‐6 secretion.…”
Section: Introductionmentioning
confidence: 71%